AMERICAN ENSLAVEMENT AS SEEN IN NARRATIVE OF THE LIFE OF FREDERICK DOUGLAS & IN THE INTERESTING NARRATIVE OF THE LIFE OF OLAUDAH EQUIAO - Suparman Suparman (Kajian Linguistik dan Sastra, 2005)
Mimetic approach is used in this study to reveal the practice of slavery depicted in two novels "narrative of the Life of Frederick Douglas" and "The Interesting Narrative of the life of Olaudah Equiao". The findings show that novels have common ground that is the practice of the slavery of blacks Africans by the whites in America. In some aspects, the slaveholders treated their slave inhumanly, savagely, and brutally. The slaves were really treated like animals in the ways of providing them food, shelter. clothes, and dispensation of rest. They were forbiden to learn of how to write and read. They were forced to work hard without having enough rest. However, when they got wage, they had to give it to their masters. Female slaves were whipped and tortured savagely, and their children were tortured to death. These are the examples of the brutality of the slaveholders.Key words: slavery, slaveholders, slaves, inhumanity, discrimination, and oppression